Analysis Factor Associated Tuberculin Test in Children Contact Tuberculosis History - Tika Triharinni; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2014)
Tuberculosis in children can’t be separated from the history of contact with positive acid fast bacteria smear in tuberculosis patients as a source of infection. Tuberculin Skin Test (TST) is a very supportive method in the early diagnosis of tuberculosis because it has high sensitivity and specificity. The aims of this study was to identify and analyze the risks TST results among children who had contact with patients with smear-positive tuberculosis in Public Health Center (PHC) of Bangil and Raci, Pasuruan. The design of this study was cross sectional using systematic random sampling technique. Sample were drown from children with history of contacts with smear positive tuberculosis patients during 2012. This studies was from January until Juni 2013. The independent variables included age, sex, BCG immunization status, nutritional status, the average duration of exposure per day and residential density, the dependent variable was the TST. It was found that from the study the results that a positive TST was 28.57%. There was a significant relationship between age, nutritional status, the average duration of exposure per day, residential density of the tuberculin test. The conclusion of this research is male and a dense residential density increases the risk of a positive TST, while a good nutritional status is a protective factor for results of TST positive.